Down-regulation of respiration in pear fruit depends on temperature - Ho, Quang Tri (Journal of experimental botany, 2018)
The respiration rate of plant tissues decreases when the amount of available O2 is reduced. There is, however, a debate on whether the respiration rate is controlled either by diffusion limitation of oxygen or through regulatory processes at the level of the transcriptome. We used experimental and modelling approaches to demonstrate that both diffusion limitation and metabolic regulation affect the response of respiration of bulky plant organs such as fruit to reduced O2 levels in the surrounding atmosphere. Diffusion limitation greatly affects fruit respiration at high temperature, but at low temperature respiration is reduced through a regulatory process, presumably a response to a signal generated by a plant oxygen sensor. The response of respiration to O2 is time dependent and is highly sensitive, particularly at low O2 levels in the surrounding atmosphere. Down-regulation of the respiration at low temperatures may save internal O2 and relieve hypoxic conditions in the fruit